The gyromagnetic factor of elementary particles and non-minimal coupling - Morais, Jefferson; Accioly, Antônio [UNESP]; Helayël-Neto, José Abdala; Turcati, Rodrigo (Sissa Medialab Srl, 2009)
In this work we investigate a possible magnetic moment generation for massive neutral particles with spins-1 and -2 coupled non-minimally, in a specific way, to an external electromagnetic field. It is found that, in the nonrelativistic limit, these particles present g = 1. This result, worked out in the framework of Relativistic Quantum Mechanics, seems to suggest that g = 1 for all massive and neutral particles of any spin ≤ 2. We also compare with the results obtained for massive charged particles of spins-1 and -2, in the same regime (nonrelativistic), in order to investigate the role played by the spin separetely from the charge. Copyright © owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.